2022
DOI: 10.1002/casp.2660
|View full text |Cite
|
Sign up to set email alerts
|

Critical action among Asian and Hispanic/Latinx youth: Identifying a multidimensional measure and exploring within‐group differences

Abstract: Critical action-behaviours aimed at dismantling systems of oppression-must be examined within youths' racialized experiences and should incorporate cultural and sociohistorical factors. We considered an expansive list of items capturing youth behaviours to create a novel four-factor (service, community change, expression, and care) measure of critical action for Asian and Hispanic/Latinx youth. Multiple distinct profiles of critical action were identified within both racial-ethnic groups, and associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Including youth critical consciousness specifically would give an important window into mechanisms by which intergenerational transmission of critical consciousness from parent to child occurs, as well as the possibility to examine concordance and discrepancies between parents’ and children’s levels of critical consciousness (Heberle et al, 2020). Initial evidence from youth self-report indicates that greater parental civic action is associated with high and/or emerging civic action among Asian and Latinx youth (Suzuki et al, 2023), but more work is needed from the parent perspective and using multiple reporters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including youth critical consciousness specifically would give an important window into mechanisms by which intergenerational transmission of critical consciousness from parent to child occurs, as well as the possibility to examine concordance and discrepancies between parents’ and children’s levels of critical consciousness (Heberle et al, 2020). Initial evidence from youth self-report indicates that greater parental civic action is associated with high and/or emerging civic action among Asian and Latinx youth (Suzuki et al, 2023), but more work is needed from the parent perspective and using multiple reporters.…”
Section: Discussionmentioning
confidence: 99%
“…Within each group, we also assess the extent to which nativity status may impact critical consciousness. In a recent study focused on profiles of critical action among Latinx and Asian adolescents, Suzuki et al (2023) not only found evidence of slightly different patterns of critical action between groups but also found that being born in the United States was associated with being in the profile highest in critical action for Asian youth and a less active profile among Latinx youth. A body of research shows that immigrant individuals, including immigrant parents, likely have different “frames of reference” (i.e., thinking of their heritage culture) when moving through and engaging with various social systems in their host country (Ogbu, 2014).…”
Section: Critical Consciousnessmentioning
confidence: 99%
“…Colleges also provide resources to gain skills, knowledge, and abilities that can promote sociopolitical engagement (Watts & Halkovic, 2022). For instance, having peers involved in civic engagement, opportunities to address sociopolitical issues at schools, and facilitators in school organizations with high self-efficacy in discussing sociopolitical issues have been related to greater civic engagement and more frequent sociopolitical discussions (Poteat et al, 2019; Suzuki et al, 2023).…”
Section: Sociopolitical Discussion and Civic Engagementmentioning
confidence: 99%
“…Such external factors may be particularly salient for high school students, who typically still lack some autonomy in their lives due to their age. It will be important for future work to explore critical action in context and especially to consider what barriers youth may perceive to participating in critical action (Suzuki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%